Pengaruh Pelatihan Terhadap Peningkatan Produktivitas Kerja Karyawan Pada PT. Raya Sugarindo Inti Tasikmalaya - Gugum Gumilar (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
This study aims to find out the training conducted for employees, employee productivity influence the impact of training on increasing employee productivity, and obstacles faced by PT. Raya Sugarindo Inti Tasikmalaya in conducting training and how to overcome them. The research method used in this research is explanatory research explaining causal relationship between independent variable (training) and dependent variable (work productivity) with data collection technique using interview, observation, spreading of questionnaire, and library study. This study uses a population of 244 people. While the sampling technique used is a random sampling technique, where samples taken from some of the population of 71 people. The results showed that Training Implementation has significant effect on the Increasing Employee Productivity PT. Raya Sugarindo Inti Tasikmalaya, judging from the determinants, the factors of measuring and influencing factors with the indicator is the development, use of time and the work achieved.